Mitigation of safety vulnerability of people and property from the effects of explosions of explosive materials in the Serbian Army - Stojanović, Dejan S.; Stojilković, Petar Lj. (Vojnotehnički glasnik / Military Technical Courier, 2015)
The aim of the research is to provide proactive mitigation of safety risk to people and property of the effects of explosions of explosive materials in the Serbian Army based on a large number of relevant collected data. Achieving these research goals requires the use of appropriate methods and techniques for understanding and studying the existing theoretical and practical solutions as well as proposing new solutions in the area of ​​interest. The research includes possibilities to mitigate risk to people and property from the effects of explosive material explosions. These possibilities aim at reducing danger, risk and threat to the population, their property and the environment, as well as at mitigating the consequences of possible emergencies. The following methods have also been discussed: avoidance, retention, reduction, division, transfer and reduction of hazards, risks and threats, where for each method a detailed theoretical explanation is provided with appropriate examples of good practice. The formulated hypothesis is also being proven, with the aim to – with a scientific objectivity towards one’s own research results - accept or reject the proposed methods.
Keywords: threat; danger; army; property; explosive